2013
DOI: 10.4046/trd.2013.74.4.151
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Alveolar Hemorrhage

Abstract: Diffuse alveolar hemorrhage (DAH) is a life-threatening and medical emergency that can be caused by numerous disorders and presents with hemoptysis, anemia, and diffuse alveolar infiltrates. Early bronchoscopy with bronchoalveolar lavage is usually required to confirm the diagnosis and rule out infection. Most cases of DAH are caused by capillaritis associated with systemic autoimmune diseases such as anti-neutrophil cytoplasmic antibody-associated vasculitis, anti-glomerular basement membrane disease, and sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
149
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(158 citation statements)
references
References 23 publications
2
149
0
7
Order By: Relevance
“…Several case reports, primarily those based on early autopsy or lung biopsy during the recovery state of the disease, have shown that ICmediated systemic vasculitis is one of the most common causes of SLE-related DPH (38). However, some SLE cases have presented with DPH without pulmonary IC-deposition or serologic disease activity (2).…”
Section: /2mentioning
confidence: 99%
“…Several case reports, primarily those based on early autopsy or lung biopsy during the recovery state of the disease, have shown that ICmediated systemic vasculitis is one of the most common causes of SLE-related DPH (38). However, some SLE cases have presented with DPH without pulmonary IC-deposition or serologic disease activity (2).…”
Section: /2mentioning
confidence: 99%
“…The causes of diffuse alveolar hemorrhage can be divided into cases associated with capillaritis and those without (Table 2) [7][8][9]. The patient's initial diagnosis prior to this admission was idiopathic pulmonary hemosiderosis, a diagnosis of exclusion, based on initial biopsy where no vessel damage seen.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the patient is currently waiting on compatible cord blood HSCT. Capillaritis is generally associated with systemic autoimmune disease, and capillaritis as an isolated entity is relatively rare [7][8][9]. However, autoimmune diseases are common in WAS (22% to 77%) [5,6] and vasculitis is a known complication of WAS occurring in approximately 20% of patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…[1] Морфологические изменения при альвеолярном геморрагическом синдроме могут носить как общий, так и специфический характер. M. Park предлагает вы-делять три гистопатологических паттерна при диф-фузном альвеолярном кровоизлиянии у детей: альвео-лярный геморрагический синдром, ассоциированный с васкулитом или капиляритом, -наиболее частый, характерный для системных заболеваний и васкулитов; альвеолярный геморрагический синдром, не сопрово-ждающийся воспалением или васкулитом, характер-ный, в частности, для идиопатического гемосидероза легких; альвеолярный геморрагический синдром, ас-социированный с другими процессами или состояния-ми, сопровождающийся прямым выходом эритроцитов в ткань легкого без признаков васкулита, свойственный токсическим или лекарственным повреждениям [2].…”
unclassified